New recurrent balanced translocations in acute myeloid leukemia and myelodysplastic syndromes: Cancer and leukemia group B 84611. Issue 4 (10th December 2012) - Walker, Alison; Mrózek, Krzysztof; Kohlschmidt, Jessica; Rao, Kathleen W.; Pettenati, Mark J.; Sterling, Lisa J.; Marcucci, Guido; Carroll, Andrew J.; Bloomfield, Clara D.
Abstract Acquired chromosome abnormalities in patients with acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS) are among the most valuable determinants of diagnosis and prognosis. In search of new recurrent balanced translocations, we reviewed the Cancer and Leukemia Group B (CALGB) cytogenetics database containing pretreatment and relapse karyotypes of 4, 701 adults with AML and 565 with MDS who were treated on CALGB trials. We identified all cases with balanced structural rearrangements occurring as a sole abnormality or in addition to one other abnormality, excluded abnormalities known to be recurrent, and then reviewed the literature to determine whether any of what we considered unique, previously unknown abnormalities had been reported. As a result, we identified seven new recurrent balanced translocations in AML or MDS: t(7;11)(q22;p15.5), t(10;11)(q23;p15), t(2;12)(p13;p13), t(12;17)(p13;q12), t(2;3)(p21;p21), t(5;21)(q31;q22), and t(8;14)(q24.1;q32.2), and additionally, t(10;12)(p11;q15), a new translocation in AML previously reported in a case of acute lymphoblastic leukemia. Herein, we report hematologic and clinical characteristics and treatment outcomes of patients with these newly recognized recurrent translocations. We also report 52 unique balanced translocations, together with the clinical data of patients harboring them, which to our knowledge have not been previously published. We hope that once the awareness of their existence is increased, some of these translocations may become recognized as novel recurring abnormalities. Identification of additional cases with both the new recurrent and the unique balanced translocations will enable determination of their prognostic significance and help to provide insights into the mechanisms of disease pathogenesis in patients with these rare abnormalities. © 2012 Wiley Periodicals, Inc.